Market Relocation of Medan Labuhan - M. J. I. Nasution; Nelson Siahaan (Talenta Publisher, 2018)
With the needs of the growing community in the District of Medan Labuhan impact on improving people's living standards & population growth. The increase is also in line with the growing demand of the provision of facilities and infrastructure because the higher the level of life of a person, the higher the demands on the provision of facilities, especially in service facilities and commerce. Therefore it is needed a container that can meet the needs of the place of shopping which is realized through